(untitled) (Research, Society and Development, 2023)
Occupational exposures to potentially contaminated biological materials are a serious risk to professionals in their workplaces. Studies developed in this area of medicine and health show that accidents involving blood and other organic fluids correspond to the most frequently reported exposures. Workers, whether health workers or not, in health establishments are at risk of suffering accidents with sharps due to the complexity of the activities developed. In order to identify the profiles of workers injured with sharps. The methodology was based on an integrative review on the question "how can we minimize accidents with sharps in various areas of health”. Its general objective is to describe the occurrences of accidents with sharps and preventive measures so that it can minimize the occurrence among workers in the health area. With the specific objective to discuss the diseases that can be acquired by professionals who are victims of accidents with sharp objects. The study in which it is a literature review based on subtracted articles in recent years. It concludes that it is necessary to take preventive and educational measures on biosafety, emphasizing the use of personal protective equipment and disposal of contaminated materials.